PERAN ADVOKAT DALAM PENANGANAN PERKARA TINDAK PIDANA PORNOGRAFI - , MUHAMMAD AIZ YAHYA R ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Humans were created as social beings and will always interact with each other . Humans are social beings can not live alone , then they will tend to live in groups . Differences of opinion and interest that can lead to a dispute often happened in human interaction . With the dispute disputing parties tend to blame the disputing parties with her and always seek the truth and justice . Indonesia is a country of law . This statement is contained in Article 1 ( 3 ) Constitution 1945 , . Law always aspire to justice and Indonesia is the Indonesian State law also always aspire to justice . Internship has the objectives such aims to produce graduates of associate experts in the field of law that has sufficient basic legal expertise and skills in the field of legal and office administration , competent and professional and / or can help people to gain access in the field of law and justice . Benefits internship is to add insight and ability in the field of jurisprudence and the internship in the office of the Advocate will recognize the wider legal profession because the street vendors in the Office of the Advocate when participating in the trial to proceed more familiar with how professional writers Judge , Prosecutor , and the Registrar . Writer not only obtained experiences when the street vendors in the office of the Advocate, but also can recognize a wide variety of other professions such as Notary Public , Police , and the Corruption Eradication Commission. Based on reflection \" Advocate Role In Crime Case Handling Pornography \" can know how big a role in his defense lawyers to protect the rights of those who seek justice proceed .